The Effect of Type and Ratio of Hardener and Curing System on the Curing Characteristics of Epoxy Resin - hesty eka mayasari (Jurnal Teknologi Proses dan Inovasi Industri, 2022)
Epoxy has many advantages and it is widely used in various fields. Hardener is a curing agent to form cured epoxy. The type and composition of the hardener and the curing system need to be studied to get the right formulation and process. This study used hardeners that are common in the market, i.e. cycloaliphatic amine (CAA) and polyaminoamide (PAA). Mixing of epoxy and hardener was done manually using room temperature vulcanization (RTV) and heating curing systems. This study aims to study the effect of the type and ratio of hardener and curing system on the curing characteristics of the epoxy resin. CAA hardener formed cured epoxy at room temperature with ratio epoxy:CAA 60:40. PAA hardener doesn’t formed cured epoxy at room temperature. The heating in curing process formed cured epoxy with epoxy:hardener (CAA or PAA) ratio of 80:20, 60:40, 40:60. CAA can be used at room temperature RTV with a ratio of 60:40 to get an efficient process